The Gods as Latent Causes: A Statistical Inference Theory of Religion - Rigoli, Francesco (The international journal for the psychology of religion, 2025)
The statistical brain hypothesis posits that the brain constructs probabilistic models of the environment. Here we examine whether this perspective can provide any insight on religion. We propose that religious ideas represent an attempt to explain away residuals, that is, to explain discrepancies between observations and predictions. The framework postulates probabilistic generative models where gods are described by latent variables whose possible states correspond to the actions available to the gods. As examined in the paper, our proposal offers a plausible interpretation of typical religious phenomena such as miracles, omens, and divination. Moreover, it captures important characteristics of religious beliefs including the notion that gods control multiple spheres of reality, are organized hierarchically, and control aspects that are salient for believers. Besides offering an intriguing new perspective on religion, the paper corroborates the possibility that the statistical brain hypothesis represents a unifying theory of the mind.